Retinal imaging using commercial broadband optical coherence tomography. Issue 3 (21st September 2009) - Tanna, Hitesh; Dubis, Adam M; Ayub, Nazia; Tait, Diane M; Rha, Jungtae; Stepien, Kimberly E; Carroll, Joseph
Abstract : Aims: To examine the practical improvement in image quality afforded by a broadband light source in a clinical setting and to define image quality metrics for future use in evaluating spectral domain optical coherence tomography (SD-OCT) images. Methods: A commercially available SD-OCT system, configured with a standard source as well as an external broadband light source, was used to acquire 4 mm horizontal line scans of the right eye of 10 normal subjects. Scans were averaged to reduce speckling and multiple retinal layers were analysed in the resulting images. Results: For all layers there was a significant improvement in the mean local contrast (average improvement by a factor of 1.66) when using the broadband light source. Intersession variability was shown not to be a major contributing factor to the observed improvement in image quality obtained with the broadband light source. We report the first observation of sublamination within the inner plexiform layer visible with SD-OCT. Conclusion: The practical improvement with the broadband light source was significant, although it remains to be seen what the utility will be for diagnostic pathology. The approach presented here serves as a model for a more quantitative analysis of SD-OCT images, allowing for more meaningful comparisons between subjects, clinics and SD-OCT systems.